A sub-nanosecond pyrometer with broadband spectral channels for temperature measurement of dynamic compression experiments. (31st May 2022) - Wu, Jian; Li, Jiabo; Li, Jun; Zhou, Xianming; Weng, Jidong; Liu, Shenggang; Tao, Tianjiong; Ma, Heli; Tang, Longhuang; Gao, Zhipeng; Wang, Xiang; Tao, Peidong; et al.
Highlights: A broadband optical pyrometer with a rise time of ∼70 ps was developed. An improved calibration procedure and data processing method was proposed. Deviation in the dynamic temperatures determined by the pyrometer was less than 2%. The pyrometer can be used to measure the temperature of laser shocked matter. Abstract: Time-resolved temperature measurement of dynamic-compressed material is critical in the high-pressure research fields. For higher temporal resolution requirement of the dynamic experiments, a broadband optical pyrometer was developed, with a rise time of ∼70 ps and a measurable temperature range of 2500 K to higher than 10000 K. Expanding the detecting bandwidth to 100 nm∼300 nm for each channel, sensitivity of the detection system increases by nearly one order of magnitude compared to the conventional configuration. An improved temperature calibration procedure and data processing method was proposed, and temperature results of the shock compression experiments using a light gas gun were identical to the simultaneous measurements by a narrowband pyrometer. The dynamic radiation from the laser shocked matter also can be perfectly captured by the developed pyrometer, and the temporal profile of temperature agreed well with the shock velocity profile in both the shape and the duration time.